Effect of a Short Hiit Program with Specific Techniques on Physical Condition and Activity During Simulated Combat in National-Level Boxers - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The present study investigated the effect of an additional short-duration HIIT program using boxing-specific techniques on activity during a simulated competition. Additionally, we investigated the impact on physical fitness, specifically aerobic performance and lower-body muscle power. Sixteen boxers were randomized into a control (n = 8) or experimental groups (n = 8). The experimental protocol consisted of 3 blocks of 5 repetitions of 30s all-out effort, with 6s recovery between repetitions and 1 min rest interval between blocks, conducted 3 days per week for 4 weeks. A two-way (group, two levels; moment, two levels) analysis of variance with repeated measure-ments in the second factor was used. For the experimental group, there was a change in body mass (ES = −0.13 (trivial)), body fat percentage (ES = −0.12 (trivial)), VO2max (ES = +0.42 (small)), CMJ (ES = +0.12 (trivial)), CMJ-left (ES = −0.11 (trivial)), CMJ-right (ES = +0.22 (trivial)), actions (ES = +0.68 (moderate)), time (ES = −0.29 (small)) and punches (ES = +0.56 (moderate)). For the control group, there was a change in body mass (ES = +0.04 (trivial)), body fat percentage (ES = −0.12 (trivial)), VO2max (ES = +0.11 (trivial)), CMJ (ES = −0.27 (small)), CMJ-left (ES = −0.39 (small)), CMJ-right (ES = +0.08 (trivial)), actions (ES = +0.08 (trivial)), time (ES = −0.65 (moderate)) and punches (ES = −0.57 (moderate)). The punches variable was significant concerning group-by-time interaction (F1,14 = 11.630; p = 0.004; n2 = 0.454). The present study indicated that the addition of a boxing-specific HIIT program is effective to increase the number of punches during a simulated match. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.